Integration of in vitro allergy test results and ratio analysis for the diagnosis and treatment of allergic patients (INTEGRA). Issue 7 (16th September 2021) - Pascal, Mariona; Moreno, Carmen; Dávila, Ignacio; Tabar, Ana I.; Bartra, Joan; Labrador, Moisés; Luengo, Olga
Abstract: The introduction of molecular diagnosis into routine clinical practice has substantially improved the diagnosis and management of allergic patients by allowing clinicians to precisely identify the allergenic molecule responsible for immunoglobulin E (IgE)‐mediated allergies. However, it can be challenging to accurately interpret the results of molecular assays, partly due to the limited evidence base. In this context, a panel of experts with extensive experience in interpreting in vitro measures of total and serum specific IgE reviewed the available scientific evidence. After this review, the panel selected a series of representative case studies to demonstrate how determination of specific and total IgE values and the relationship between them (ratio analysis) can add value to the diagnostic process by more precisely defining the patient's sensitization profile. Finally, the experts developed a series of recommendations on the clinical application of ratio analysis to optimize and complement the classical approach to allergy diagnosis.